2013
DOI: 10.1590/s1981-67232013005000019
|View full text |Cite
|
Sign up to set email alerts
|

Eficiência de materiais encapsulantes naturais e comerciais na liberação controlada de probiótico encapsulado

Abstract: ResumoO probiótico composto por Saccharomyces cerevisiae foi encapsulado pelo método de imobilização em cubos de ágar-ágar, em diferentes gomas comerciais e mucilagens, com o objetivo de proporcionar liberação controlada do microrganismo durante simulação gastrointestinal in vitro. Foram utilizados ágar-ágar (A-A), alginato (ALG), iota-carragena (I-CAR), goma arábica (ARA), taro (TARO), inhame (INH), linhaça (LIN) e quiabo (QUI) como materiais encapsulantes. Durante a simulação, foi realizada a contagem da lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Rodrigues et al [ 88 ] encapsulated the probiotics Lactobacillus casei LC-01 and L. casei BGP in sodium alginate microspheres composed of linseed and okra mucilages, botryosphaeran, and commercial fructo-oligosaccharides (FOS) by the extrusion technique in calcium chloride. Laurenti and Garcia [ 89 ] used okra mucilage to encapsulate the probiotic Saccharomyces cerevisiae by the method of immobilization in agar-agar cubes. The results showed that this mucilage is a natural and alternative encapsulating material and is more efficient than the commercial gums used for this purpose.…”
Section: Food Technologymentioning
confidence: 99%
“…Rodrigues et al [ 88 ] encapsulated the probiotics Lactobacillus casei LC-01 and L. casei BGP in sodium alginate microspheres composed of linseed and okra mucilages, botryosphaeran, and commercial fructo-oligosaccharides (FOS) by the extrusion technique in calcium chloride. Laurenti and Garcia [ 89 ] used okra mucilage to encapsulate the probiotic Saccharomyces cerevisiae by the method of immobilization in agar-agar cubes. The results showed that this mucilage is a natural and alternative encapsulating material and is more efficient than the commercial gums used for this purpose.…”
Section: Food Technologymentioning
confidence: 99%